2014
DOI: 10.3920/wmj2013.1672
|View full text |Cite
|
Sign up to set email alerts
|

Application of mycotoxin adsorbent to cattle feed contaminated with zearalenone: urinary zearalenone excretion and association with anti-Müllerian hormone

Abstract: This study investigated (1) protective effects of a commercially available mycotoxin adsorbent (MA) and (2) endocrine effects of in vivo exposure to zearalenone (ZEA) in cattle. The sample included a Japanese Black female cattle herd (MYT herd) that displayed persistently high urinary ZEA concentrations. A second herd (NM herd) was used as a control. Three groups from each herd were assessed: MX (n=6; MA mixed with concentrate), TD (n=6; MA applied as topdressing with the concentrate), and a positive control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 28 publications
1
23
2
Order By: Relevance
“…Recently, in a preliminary study, we reported the possible effects of in vivo exposure to this level of contamination of ZEA and its metabolites on the population of antral follicles, as assessed by significantly lower serum AMH levels measured in the stocked serum samples from the above‐mentioned ZEA‐contaminated herd (Fushimi et al. ). Therefore, the objective of this study was to evaluate the relationship between urinary ZEA, including its metabolites, and serum AMH concentrations in commercial breeding cattle herds exposed to lower ZEA contamination levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in a preliminary study, we reported the possible effects of in vivo exposure to this level of contamination of ZEA and its metabolites on the population of antral follicles, as assessed by significantly lower serum AMH levels measured in the stocked serum samples from the above‐mentioned ZEA‐contaminated herd (Fushimi et al. ). Therefore, the objective of this study was to evaluate the relationship between urinary ZEA, including its metabolites, and serum AMH concentrations in commercial breeding cattle herds exposed to lower ZEA contamination levels.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the experiment, the ZEA level in the dietary feed of both herds was measured via liquid chromatography‐tandem mass spectrometry (LC/MS/MS), as previously described (Fushimi et al. ). The concentrations of ZEA in the fescue grass, oats hay and concentrates fed to cows in Herd 1 were <0.01, 0.1 and <0.01 ppm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several field or case reports in which a direct relationship between ZEA exposition levels and symptoms of estrogenic effects was not found were reported [ 260 ], suggesting this might reflect the variability in rumen degradation of ZEA. Recent experiences tried to relate exposure of dairy cows to ZEA contaminated diet on herd level by measuring urinary metabolites [ 261 , 262 , 263 ]. Authors suggested that monitoring urinary ZEA concentrations could represent an useful tool to predict animal exposure to ZEA and other Fusarium toxins.…”
Section: Effect Of Mycotoxins Ingestion On Ruminants: Inmentioning
confidence: 99%
“…Those reports are mainly based on clinical symptoms observed in field studies or following the experimental administration of mycotoxin to cattle, occasionally with concomitant biochemical analysis. However, risk evaluations concerning the metabolic status of cattle exposed to mycotoxin contamination are lacking [ 3 ].…”
Section: Introductionmentioning
confidence: 99%